EXPLORING INTERSECTIONALITY IN AMERICAN AND BRITISH FICTION: DOI: https://doi.org/10.5281/zenodo.17400051 (Contemporary Journal of Social Science Review, 2025)
This article  analyzes representations of transgender and non-binary identities through a transnational, comparative literary analysis of Girl, Woman, Other by Bernardine Evaristo, and Middlesex by Jeffrey Eugenides. It investigates how the experiences and identities of trans characters in British and American literature are shaped through the lens of intersectionality, particularly at the intersections of race, class, gender, and national context. The study pays particular attention to the distinct narrative frameworks established by each text. Middlesex constructs trans identity within a model that is medicalized, binary, and biologically deterministic, where gender transition and transformation are normalized as a journey defined by genetics and sanctioned by institutions. In contrast, Girl, Woman, Other addresses self-definition, gender fluidity, and identification, situating trans and non-binary identities within a broader socio-political post-colonial context. Finally, the close reading of these texts demonstrates that Girl, Woman, Other promotes disruptive narratives in its representation of marginalized gender identities, particularly those of Black and working-class individuals, while Middlesex reinforces and engages with a dominant ideological position in Western narratives that characterize trans identity as white, middle-class, and legitimized by medical establishments.